Genetics and Ecology of the Silvered Leaf Monkey (Genus Trachypithecus) from Malaysia - Faisal Ali, Anwarali Khan; Henry, Bernard; Wan Nur Syafinaz, Wan Azman; Lim, Zhi Han (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Genetic information is major component in formulating a better conservation strategy of the Silvered Leaf Monkey. In Malaysia, there are three species under genus Trachypithecus namely T. cristatus, T. selangorensis and T. obscurus. This current study primary focus is on the Silvered Leaf Monkey which is the only member of this genus found in Borneo. The population trend of Silvered Leaf Monkey (Trachypithecus cristatus) is reported to be near threatened due to human activities such as deforestation. Recent study has separated Trachypthecus cristatus from Peninsular Malaysia as a separate species which is now recognized as Trachypithecus selangorensis that is endemic to Peninsular Malaysia. This study aims to better understand this separation as well as the population status in Borneo via molecular tools. Silvered Leaf Monkey feaces has been collected across multiple locality in Borneo to access their DNA to better understand genetic variation across multiple population in Borneo. Genetic variation is currently being assessed using mitochondrial (Cytochrome b, and Cytochrome Oxidase subunit I and II, control region and paternal (sex determining region -SRY) markers. Our preliminary genetic result showed that no geographic structure was observed within Borneo indicating high gene flow between populations. When compared to other species of non-human primates, the genetic diversity of silvered leaf monkey can be considered as moderate. The complete result of genetic and ecology of this species is expected to be completed upon sampling in Peninsular Malaysia earlier next year.